101 secrets a good dad knows - Browder, Walter (Rutledge Hill P. NashvilleUS, 2000)
Seeks to equip fathers with the skills necessary for teaching their children to perform 101 tasks including: identifying six intercontinental aeroplanes by observing their wings and tails; carving a whistle; whistling through their fingers; climbing a tree; walking on stilts; changing the sparkplug on a car; using the rare letters in Scrabble; identifying a good puppy; and picking up a crab.